Continuous glass fiber composite material for battery box cover plate and preparation method of continuous glass fiber composite material

By using continuous glass fiber fabric fabrics and thermoplastic resin, combined with halogen -free flame retardants and porcelain powder, solve the problem of difficulty in processing, high cost, and impact resistance in the existing materials. High -performance battery box cover material is suitable for new energy vehicle battery box cover.

CN119371745APending Publication Date: 2025-01-28NANJING JULONG SCIENCE & TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411479758.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing glass fiber reinforced flame-retardant polypropylene composite materials have problems such as processing difficulties, high material costs and poor impact resistance due to fiber discontinuity, which cannot meet the performance requirements of the battery box cover of new energy vehicles.

Method used

The continuous glass fiber fabric and thermoplastic resin are used to compound, and continuous glass fiber composite materials are made through the three -dimensional weaving process. The battery box cover material.

Benefits of technology

The high fiber content, excellent mechanical performance and flame retardant performance of the material can be realized. It can meet or even exceed the performance requirements of the same or lower metal material units, and it is suitable for new light -quality high -strength materials that are suitable for thin -walled structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097025600000101
    Figure BDA0005097025600000101
  • Figure BDA0005097025600000111
    Figure BDA0005097025600000111
Patent Text Reader

Abstract

The invention provides a continuous glass fiber composite material for a battery box cover plate and a preparation method thereof, and the composite material comprises the following components in parts by weight: 10-50 parts of thermoplastic resin, 10-70 parts of a continuous glass fiber woven fabric, 5-20 parts of a halogen-free flame retardant, 1-20 parts of porcelainized powder, 1-5 parts of an interfacial compatibilizer, 1-20 parts of a microstructure adjusting auxiliary agent, and 0.1-1 part of an antioxidant. The continuous glass fiber woven fabric is prepared from glass fiber direct yarns with the linear density of 300tex-2400tex through a three-dimensional weaving process, and the porcelainized powder is prepared from at least one of a boron compound and low-softening-point glass powder and mineral filler. The continuous fiber woven fabric and the thermoplastic resin are compounded and synergistically complemented to jointly enhance the mechanical property of the material, metal materials can be partially replaced, and the performance requirement is met or even exceeded under the condition that the unit weight is equal to or lower than that of the metal materials; therefore, a novel light high-strength material suitable for a thin-wall structure and oriented to a new special structure is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a continuous glass fiber composite material for a battery box cover and a preparation method thereof. Background Art

[0002] At present, with the increasing environmental awareness in various countries, the market share of new energy vehicles has gradually increased, and the demand for materials around new energy vehicles in the material market has gradually increased. New energy vehicle battery peripheral materials have become an emerging material market. Due to the particularity of the battery part of new energy vehicles, the battery pack design has extremely high safety requirements. Therefore, the materials used in the battery part, whether structural parts or functional parts, have high requirements for their mechanical properties and flame retardant properties. For battery pack cover materials, polymer composite materials have been used to replace traditional metal materials to achieve the purpose of weight reduction. Among the replaceable polymer composite materials, there are thermosetting SMC materials and flame-retardant PPO, PC / ABS, PA and other engineering plastics. However, the above two materials have defects in the application process. For example, thermosetting SMC materials cannot be recycled after use, which is easy to cause environmental pollution and material waste; for flame-retardant engineering plastics, they have the disadvantages of difficult processing and expensive materials. Therefore, the above two materials are difficult to become the best choice for battery pack cover materials of new energy vehicles.

[0003] Ceramic polymer composites are a type of composite material prepared by adding ceramic additives to polymer resins and melt blending. They are a new type of fireproof, flame-retardant and thermal runaway-proof material. Ceramic polymer composites have excellent resistance to high and low temperatures, electrical insulation, ozone resistance, weather resistance, and arc resistance. When encountering high-temperature flame ablation, they can form a hard ceramic-based protective layer, thereby protecting the protected object from damage. Specifically, ceramic polymer composites have the excellent properties of ordinary polymer composites at room temperature. In the medium and low temperature stage, they rely on the ablation resistance of the ablation-resistant polymer material itself to prevent heat. In the high temperature stage, when the ambient temperature exceeds the ceramic temperature node of the material, the composite material undergoes a ceramic transformation to form a ceramic protective layer, which relies on the high heat resistance of the ceramic material itself to play a role in thermal protection. In addition, the composite material has a certain strength and can withstand a certain amount of heat flow erosion, thereby protecting the inside of the material from high temperature damage.

[0004] Polypropylene (PP) is a widely used general-purpose plastic with excellent comprehensive performance and molding processability and relatively low price. Adding glass fiber can not only make up for the performance defects of polypropylene, but also further reduce the material cost. It is one of the current focuses of polypropylene material modification for automobiles. After ordinary polypropylene is reinforced and flame-retardant modified with glass fiber, its performance can meet the strict requirements of the safety design of new energy vehicle battery packs. Compared with SMC materials and reinforced flame-retardant engineering plastics, glass fiber reinforced flame-retardant polypropylene composite materials have the advantages of simple processing, easy uniform distribution of glass fiber, and low material price. In order to meet the strict requirements of the safety design of new energy vehicle battery packs, glass fiber reinforced flame-retardant polypropylene composite materials need to add 20-30phr of flame retardant and 20-40phr of glass fiber to its composition. The proportion of its filling material components is quite high, which makes processing difficult. The traditional process needs to compound the flame retardant and glass fiber with the matrix material separately through a two-step method, which has a long manufacturing cycle, low yield, and high material cost, which is not conducive to the large-scale promotion of the composite material in the fiercely competitive market.

[0005] Existing patent document CN109181101 discloses a glass fiber reinforced flame-retardant polypropylene composite material for a battery pack cover, which transports thermoplastic resin (including homopolymer polypropylene, copolymer polypropylene, polyethylene, nylon 6 or nylon 66) and additives to a gravity mixing and metering unit for mixing, and then forms a waterfall-like polymer film through a film die head. The polymer film is directly fed into the opening of a twin-screw compounding extruder, and continuous fiber roving passes through a specially designed roving frame. After preheating, dispersion and other procedures, it is introduced into the top of the polymer film and merges with the film to enter the twin-screw compounding extruder together. The roving is cut by the screw and gently mixed into the pre-melted polymer, and then directly fed into the pressing mold of the engine underbody guard plate for molding or pushed into the injection mold of the engine underbody guard plate for molding. This existing patent is a typical LFT process. The continuous fiber is first sheared and broken by a twin-screw, then mixed and extruded with the resin by a twin-screw, and then directly connected to the press mold. The extruded long glass fiber reinforced plastic is molded to form a bottom guard plate, which is actually a non-continuous fiber reinforced type. Because this process cannot mix continuous fibers during twin-screw processing, and the non-continuous fiber content of the processed fiber cannot be too high, the shear torque is too high when the fiber content is too high. Under normal circumstances, the fiber content of twin-screw processing generally does not exceed 40%, and it is impossible to make a guard plate with a high fiber content. Most of its fiber lengths are between 6-12mm. At the same time, due to the non-continuity of the fiber, the impact resistance is far inferior to that of continuous fibers.

[0006] Existing patent document 114311468 discloses a method for preparing a vehicle underbody guard plate based on a unidirectional tape of continuous fiber thermoplastic composite material. Although the fiber state in its technical solution is not sheared by a twin-screw, the interlayer bonding between its prepreg tape layers is poor.

[0007] The above-mentioned prior art shows that the use of glass fiber and flame retardant to modify polypropylene can greatly improve the performance of polypropylene, thereby expanding its application scenarios. However, the glass fiber used in the current production of glass fiber reinforced flame retardant polypropylene composite materials is not in a continuous state, and it cannot form good adhesion with thermoplastic resins. Therefore, the mechanical properties of the composite material formed by the two cannot meet the performance requirements of the battery box cover of new energy vehicles. In addition, the existing production and processing procedures are complicated and the production capacity is low, resulting in a long cycle, high energy consumption and high material cost in the production process of composite materials. Therefore, it cannot well respond to the core demand for materials in the environmental protection trend. Summary of the invention

[0008] The purpose of the present invention is to provide a continuous glass fiber composite material for a battery box cover and a preparation method thereof, which adopts a continuous fiber woven fabric and a thermoplastic resin composite, the two of which complement each other synergistically and jointly enhance the mechanical properties of the material, and can partially replace metal materials. The performance requirements are achieved or even exceeded at a unit weight equal to or lower than that of the metal material, thereby preparing a new lightweight and high-strength material suitable for thin-walled structures and oriented towards new special structures.

[0009] To achieve the above object, the present invention proposes the following technical solutions:

[0010] A continuous glass fiber composite material for a battery box cover, the composite material comprising the following components in parts by weight: 10-50 parts of a thermoplastic resin, 10-70 parts of a continuous glass fiber woven fabric, 5-20 parts of a halogen-free flame retardant, 1-20 parts of a ceramic powder, 1-5 parts of an interface compatibility agent, 1-20 parts of a microstructure adjustment aid, and 0.1-1 parts of an antioxidant;

[0011] The continuous glass fiber woven fabric is made of glass fiber direct yarn with a linear density of 300tex-2400tex by a three-dimensional weaving process;

[0012] The porcelain powder is composed of at least one of a boron compound and a low softening point glass powder and a mineral filler.

[0013] As a preferred embodiment of the present invention, it also includes 0.1-1 parts of masterbatch.

[0014] As a preferred embodiment of the present invention, the thermoplastic resin includes one or a mixture of more than one of polypropylene, nylon 6, nylon 66, polylactic acid, polycarbonate, thermoplastic polyurethane, polyester, polyphenylene sulfide, and polymethyl methacrylate.

[0015] As a preferred embodiment of the present invention, the halogen-free flame retardant includes one or a mixture of more than one of ammonium phosphate, ammonium polyphosphate, modified ammonium polyphosphate, ammonium hypophosphite, melamine and its compounds, zinc borate, montmorillonite, clay, metal hydroxide, organic phosphate compound, organic hypophosphite compound, and polyol.

[0016] As a preferred embodiment of the present invention, the mineral filler includes one or a mixture of more than one of attapulgite, bentonite, kaolin, montmorillonite, clay, clay, mica powder, talc, feldspar powder, brucite powder, magnesite powder, forsterite powder, calcium silicate borate powder, chlorite powder, pyrophyllite powder, calcite powder, limestone powder, potassium feldspar powder, wollastonite powder, spodumene powder, and terephthalite powder.

[0017] As a preferred embodiment of the present invention, the boron compound is one or a mixture of more than one of boric anhydride, borax, ammonium borate, zinc borate, and boron frit;

[0018] The low softening point glass powder includes one or a mixture of more than one of lead oxide glass powder, calcium oxide glass powder, bismuth oxide glass powder, phosphate glass powder, silicate glass powder and borate glass powder.

[0019] As a preferred embodiment of the present invention, the interfacial compatibilizer includes any one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted styrene, maleic anhydride grafted polyolefin, and maleic anhydride grafted polyolefin elastomer, and the grafting rate is 1.0%-3.0%.

[0020] As a preferred embodiment of the present invention, the structure adjustment auxiliary agent includes one or a mixture of more than one of an organic phosphate nucleating agent and a sorbitol nucleating agent.

[0021] As a preferred embodiment of the present invention, the antioxidant is one or a mixture of more than one of antioxidant 1010, antioxidant 168 and antioxidant DSTP.

[0022] A method for preparing the continuous glass fiber composite material for the battery box cover as described above comprises the following steps:

[0023] Step 1: Weaving the glass fiber direct yarn into the continuous fiber woven fabric by a weaving process, wherein the continuous fiber woven fabric includes any one of gingham, twill and satin;

[0024] Step 2: uniformly mixing the thermoplastic resin, the halogen-free flame retardant, the ceramic powder, the interfacial compatibility agent, the microstructure adjustment agent and the antioxidant according to a weight ratio to obtain a mixture, and then extruding and granulating the mixture to obtain a thermoplastic resin modified system;

[0025] Step three: preparing a continuous glass fiber composite material by laminating the continuous fiber woven fabric and the thermoplastic resin system.

[0026] The continuous glass fiber composite material for the battery box cover provided by the present invention, compared with the prior art, adopts continuous fiber woven fabrics instead of short fibers to reinforce thermoplastic resins. The use of continuous fiber woven fabrics can achieve the maximum utilization rate of the fiber's own performance, which can reach 100%, so that the continuous glass fiber composite material has more excellent mechanical properties such as bending modulus, bending strength, tensile modulus, tensile strength, impact resistance and puncture resistance. For example, under the condition of the same or less thickness as the short fiber reinforced thermoplastic composite material, the continuous glass fiber composite material of the present invention has 2-4 times higher bending strength, bending modulus, tensile strength and tensile modulus than the short fiber reinforced thermoplastic composite material. Therefore, when applied to thin-walled structures, it can meet the performance requirements at a lower cost.

[0027] In addition, the glass fiber adopts a three-dimensional woven structure, and cross-linking is generated between the fiber bundles, which can effectively prevent slippage between the glass fibers, thereby producing stronger adhesion, so that the composite material composed of continuous fiber woven fabrics and thermoplastic resins has excellent interlaminar shear strength, compression modulus and compression strength. When the product is made in molding processing directions such as compression molding and insert injection molding, the cutting pre-formed structure can be used to prevent the fiber from pulling and deforming, so as to form structurally complete bends and corner wraps.

[0028] Thermoplastic resin, interfacial compatibilizer, and microstructure adjustment additive are fully impregnated and coated on the outside of continuous glass fiber woven fabric and flame retardant. In addition, the external stress and strain effect transmitted between the ceramic powder and other additives perfectly demonstrates the material properties of glass fiber reinforcement. Among them, thermoplastic resin is a thermoplastic material. By means including but not limited to infrared radiation heating and hot mold transfer heating, the continuous glass fiber composite material can be subjected to secondary and multiple structural shaping when the temperature reaches above the melting point of the thermoplastic resin to form a product design structure.

[0029] The continuous glass fiber composite material of the present invention reaches the UL94 V-0 fireproof heat release runaway grade. When the product has thermal runaway, the flame retardant and protective materials such as ceramic powder contained in the composite material will form a ceramic protective layer on the surface of the product, thereby isolating harmful gases such as heat and smoke. At the same time, the three-dimensional woven fibers form a cross-linked support structure to prevent material collapse and high-temperature jet heat flow penetration, which can effectively reduce the harm to the surrounding product structure and personnel.

[0030] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs.

[0032] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and similar words do not indicate a quantity limitation, but indicate the existence of at least one. "Include" or "comprises" and similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.

[0033] In order to overcome the fact that the existing glass fiber thermoplastic composite materials cannot meet the various performance requirements required for the battery cover of new energy vehicles, the embodiment of the present invention provides a continuous glass fiber composite material for the battery box cover, and the composite material includes the following components by weight: 10-50 parts of thermoplastic resin, 10-70 parts of continuous glass fiber woven fabric, 5-20 parts of halogen-free flame retardant, 1-20 parts of ceramic powder, 1-5 parts of interface compatibilizer, 1-20 parts of microstructure adjustment additive, and 0.1-1 part of antioxidant. In order to meet the user's demand for different colors, 0.1-1.0 parts of masterbatch can also be added to the above formula system. The specific color can be customized according to the needs. For example, the color of the battery box cover is generally black or gray, so you can choose a masterbatch that is black or gray.

[0034] In an embodiment of the present invention, the thermoplastic resin includes one or a mixture of more than one of polypropylene, nylon 6, nylon 66, polylactic acid, polycarbonate, thermoplastic polyurethane, polyester, polyphenylene sulfide, and polymethyl methacrylate. Among them, in some preferred embodiments of the present invention, the preferred thermoplastic resin has a melt index of ≥30g / 10min at 230°C and 2.16kg.

[0035] In an embodiment of the present invention, the continuous glass fiber woven fabric is woven from glass fiber direct yarn with a linear density of 300tex-2400tex through a weaving process using a three-dimensional weaving process; preferably, the cross-section of the glass fiber direct yarn is circular or elliptical, and the diameter of the single filament is 10-20μm. The continuous glass fiber woven fabric woven from the glass fiber direct yarn includes any one of gingham, twill, and satin, and may not be limited to the above-mentioned types of woven fabrics; in some preferred embodiments of the present invention, 2 / 2 twill is selected because the fiber curvature in this woven fabric is lower than that of plain weave, so the performance of the continuous glass fiber composite material made of twill is better than that of plain weave, and under the same conditions, the performance of the former is 10% higher than that of the latter.

[0036] The halogen-free flame retardant includes one or a mixture of more than one of ammonium phosphate, ammonium polyphosphate, modified ammonium polyphosphate, ammonium hypophosphite, melamine and its compounds, zinc borate, montmorillonite, clay, metal hydroxide, organic phosphate compound, organic hypophosphite compound and polyol.

[0037] In an embodiment of the present invention, the ceramic powder is composed of at least one of a boron compound and a low softening point glass powder and a mineral filler.

[0038] Among them, the boron compound is one or a mixture of more than one of boric anhydride, borax, ammonium borate, zinc borate, and boron frit; the low softening point glass powder includes one or a mixture of more than one of lead oxide glass powder, calcium oxide glass powder, bismuth oxide glass powder, phosphate glass powder, silicate glass powder, and borate glass powder.

[0039] The mineral filler includes one or a mixture of more than one of attapulgite, bentonite, kaolin, montmorillonite, clay, mica powder, talc powder, feldspar powder, brucite powder, magnesite powder, forsterite powder, calcium silicate borate powder, chlorite powder, pyrophyllite powder, calcite powder, limestone powder, potassium feldspar powder, wollastonite powder, spodumene powder and terephthalite powder.

[0040] The interfacial compatibilizer includes any one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted styrene, maleic anhydride grafted polyolefin, and maleic anhydride grafted polyolefin elastomer, and the grafting rate is 1.0%-3.0%.

[0041] The structure adjustment auxiliary agent includes one or a mixture of organic phosphate nucleating agents and sorbitol nucleating agents.

[0042] The antioxidant is one of antioxidant 1010, antioxidant 168, and antioxidant DSTP, or a mixture of more than one of them.

[0043] The embodiment of the present invention also provides a method for preparing a continuous glass fiber composite material for a battery box cover, comprising the following steps:

[0044] Step 1: Weaving the glass fiber direct yarn into the continuous fiber woven fabric by a weaving process, wherein the continuous fiber woven fabric includes any one of gingham, twill and satin.

[0045] Step 2: uniformly mix the thermoplastic resin, the halogen-free flame retardant, the ceramic powder, the interfacial compatibility agent, the microstructure adjustment agent and the antioxidant according to a weight ratio to obtain a mixture, and then extrude and granulate the mixture to obtain a thermoplastic resin modified system.

[0046] Step three: preparing a continuous glass fiber composite material by laminating the continuous fiber woven fabric and the thermoplastic resin system.

[0047] Step 4: Design and lay the continuous glass fiber composite material obtained in step 3 according to the requirements of the battery box cover, cut or splice the continuous glass fiber composite material into the required bottom guard plate design size, and then hot-press it into a composite plate with a certain thickness and limited laying angle orientation, and cut the composite plate into a blank composite plate according to the size required by the final battery box cover.

[0048] Step 5: Heat the blank composite board to a semi-softened state, then quickly put it into the forming mold, close the mold, and press it into the part blank required for the design and shape of the battery box cover.

[0049] Step 6: Machining the blank parts into the final size of the battery box cover parts.

[0050] Example 1

[0051] The raw materials used in this embodiment are as follows:

[0052] 1. Thermoplastic resin: Use high-fluidity polypropylene PP (polypropylene with high melt index, typical melt index MFR ≥ 30g / 10min), such as SK BX3950 / 3920 / 3900, Yanshan Petrochemical's 7100 / 7780 and other copolymer polypropylene. This embodiment 1 specifically uses copolymer polypropylene with a melt index MFR of 60g / 10min (under the conditions of 230°C and 2.16Kg) from Nanjing Refinery Co., Ltd. The above thermoplastic resin has relatively good heat resistance and impact resistance, as well as low shrinkage and relatively good dimensional stability.

[0053] 2. Glass fiber direct yarn: Owens Corning SE48051200tex or 2400tex direct yarn can be used; or Jushi, Chongqing International, Taishan Fiberglass, Shandong Fiberglass, Changhai, Jiuding and other brands of glass fiber direct yarn can be used. This embodiment 1 specifically uses Jushi's glass fiber direct yarn and uses a high-speed rapier loom to make a continuous glass fiber woven fabric, specifically a 2 / 2 twill woven fabric.

[0054] 3. Antioxidant: A mixed antioxidant made of Lianlong 1010 and Lianlong 168.

[0055] The specific formulation data of this embodiment 1 is as follows:

[0056] 10 parts of thermoplastic resin, 70 parts of continuous glass fiber woven fabric, 5 parts of halogen-free flame retardant, 10 parts of ceramic powder, 2.9 parts of interface compatibilizer, 1 part of microstructure adjustment auxiliary agent, 0.11 parts of antioxidant, and 1 part of masterbatch.

[0057] The above components are made into a continuous glass fiber composite material according to the preparation method provided in the embodiment of the present invention. Specifically, the thermoplastic resin system is made into the required film by a twin-screw extruder, wherein the extruder screw diameter is 35 mm, the aspect ratio L / D is 40, the temperature of each zone of the main barrel from the feed port to the die outlet is set to 60°C, 180°C, 200°C, 210°C, 210°C, 210°C, 210°C, 210°C, respectively, the main barrel speed is 400 rpm, after melting, extrusion casting is performed, and after cooling, a film is obtained, and the film is laminated with the woven continuous glass fiber woven fabric in a flat hot press, and finally the required continuous glass fiber composite material is obtained, which is recorded as product 1, wherein the lamination conditions are 200°C-250°C, 2-20bar and processing for 5 minutes.

[0058] Example 2

[0059] 25 parts of thermoplastic resin, 28 parts of continuous glass fiber woven fabric, 20 parts of halogen-free flame retardant, 1 part of ceramic powder, 4.9 parts of interface compatibilizer, 20 parts of microstructure adjustment auxiliary agent, 1 part of antioxidant, and 0.1 part of masterbatch.

[0060] The preparation method is the same as that in Example 1 and will not be described again herein to obtain Product 2.

[0061] Example 3

[0062] 50 parts of thermoplastic resin, 10 parts of continuous glass fiber woven fabric, 10 parts of halogen-free flame retardant, 20 parts of porcelain powder, 1 part of interface compatibility agent, 8 parts of microstructure adjustment auxiliary agent, 0.5 parts of antioxidant, and 0.5 parts of masterbatch.

[0063] The preparation method is the same as that in Example 1 and will not be repeated here to obtain product 3.

[0064] Comparative Example

[0065] Taking the existing traditional discontinuous fiber reinforced thermoplastic composite material PP+GF30% as a reference, its specific formula composition is as follows:

[0066] 10 parts of thermoplastic resin, 70 parts of discontinuous glass fiber, 5 parts of halogen-free flame retardant, 10 parts of ceramic powder, 3 parts of interface compatibilizer, 1 part of microstructure adjustment auxiliary agent, 0.1 parts of antioxidant, and 1 part of masterbatch.

[0067] The preparation method of the comparative example is also the same as that of Example 1 to obtain a comparative example product.

[0068] With reference to the standard sample thickness of 4.0 mm, various properties of the products obtained in the comparative example and the products obtained in Examples 1-3 were tested. The test results are shown in Table 1 below.

[0069] Test items and standards

[0070] Tensile properties: According to ISO527-2 standard, the test rate is 2mm / min.

[0071] Bending performance: According to IS178 standard, the span-to-thickness ratio is 1:16 and the test rate is 2mm / min.

[0072] Impact performance: Tested on a simply supported beam impact tester according to ISO179-1 standard, with no notches on the specimen.

[0073] Flame retardant performance: tested according to standard UL94, the sample thickness is 1.0mm.

[0074] Table 1 Test results of Examples 1-3 and Comparative Examples

[0075]

[0076]

[0077] It can be seen from the test results of Table 1 above that compared with non-continuous fiber reinforced thermoplastic composite materials, continuous fiber reinforced thermoplastic composite materials can provide more excellent bending modulus, bending strength, tensile strength and impact resistance, wherein the tensile strength of Example 1 is 5 times that of the comparative example, significantly improving the tensile strength of the material, and the impact resistance of the embodiment is more than 3 times, which also significantly improves the impact resistance of the material; for bending modulus, bending strength, tensile modulus and tensile strength, the reason for the decrease in order from Example 1 to Example 3 may be that the proportion of thermoplastic resin in Example 3 is large and the continuous glass fiber woven fabric ratio is insufficient, so that the continuous glass fiber woven fabric cannot have enough weight to be compounded with thermoplastic resin to form an effective lamination, therefore, in order to obtain a continuous glass fiber composite material with excellent performance, it is necessary to pay attention to the ratio of thermoplastic resin to continuous glass woven fabric. In addition, the present invention adopts NP series flame retardant and porcelain powder, which can make the flame retardant test grade of the material reach 94UL V0 level, and the addition of the flame retardant can also improve the tensile performance and bending performance of the material.

[0078] In summary, the continuous glass fiber composite material of the embodiment of the present invention can achieve 2-4 times the bending strength, 2-4 times the bending modulus, and 2-5 times the tensile strength of the non-continuous fiber reinforced thermoplastic composite material under the condition that the thickness is equal to or lower than that of the latter, so that when it is applied to the battery box cover, a thin-wall structure can be adopted to meet the performance requirements at a lower cost.

[0079] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A continuous glass fiber composite material for a battery box cover, characterized in that: The composite material comprises the following components in parts by weight: 10-50 parts of thermoplastic resin, 10-70 parts of continuous glass fiber woven fabric, 5-20 parts of halogen-free flame retardant, 1-20 parts of ceramic powder, 1-5 parts of interface compatibility agent, 1-20 parts of microstructure adjustment auxiliary agent, and 0.1-1 parts of antioxidant; The continuous glass fiber woven fabric is made of glass fiber direct yarn with a linear density of 300tex-2400tex by a three-dimensional weaving process; The porcelain powder is composed of at least one of a boron compound and a low softening point glass powder and a mineral filler.

2. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: Also includes 0.1-1 part of masterbatch.

3. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The thermoplastic resin includes one or a mixture of more than one of polypropylene, nylon 6, nylon 66, polylactic acid, polycarbonate, thermoplastic polyurethane, polyester, polyphenylene sulfide, and polymethyl methacrylate.

4. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The halogen-free flame retardant includes one or a mixture of ammonium phosphate, ammonium polyphosphate, modified ammonium polyphosphate, ammonium hypophosphite, melamine and its compounds, zinc borate, montmorillonite, clay, metal hydroxide, organic phosphate compound, organic hypophosphite compound, and polyol.

5. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The mineral filler includes one or a mixture of more than one of attapulgite, bentonite, kaolin, montmorillonite, clay, mica powder, talc, feldspar powder, brucite powder, magnesite powder, forsterite powder, calcium silicate borate powder, chlorite powder, pyrophyllite powder, calcite powder, limestone powder, potassium feldspar powder, wollastonite powder, spodumene powder and terephthalite powder.

6. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The boron compound is one or a mixture of more than one of boric anhydride, borax, ammonium borate, zinc borate, and boron frit; The low softening point glass powder includes one or a mixture of more than one of lead oxide glass powder, calcium oxide glass powder, bismuth oxide glass powder, phosphate glass powder, silicate glass powder and borate glass powder.

7. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The interfacial compatibilizer includes any one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted styrene, maleic anhydride grafted polyolefin, and maleic anhydride grafted polyolefin elastomer, and the grafting rate is 1.0%-3.0%.

8. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The structure adjustment auxiliary agent includes one or a mixture of organic phosphate nucleating agents and sorbitol nucleating agents.

9. The continuous glass fiber composite material for battery box cover according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 168, and antioxidant DSTP, or a mixture of more than one of them.

10. A method for preparing a continuous glass fiber composite material for a battery box cover as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weaving the glass fiber direct yarn into the continuous fiber woven fabric by a weaving process, wherein the continuous fiber woven fabric includes any one of gingham, twill and satin; Step 2: uniformly mixing the thermoplastic resin, the halogen-free flame retardant, the ceramic powder, the interfacial compatibility agent, the microstructure adjustment agent and the antioxidant according to a weight ratio to obtain a mixture, and then extruding and granulating the mixture to obtain a thermoplastic resin modified system; Step three: preparing a continuous glass fiber composite material by laminating the continuous fiber woven fabric and the thermoplastic resin system.